DETERMINAN PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT - Bestari Dwi Handayani; Heri Yanto (University of Merdeka Malang, 2013)
The objective of this study was to identify the effect of firm size, RMC, auditor reputation and ownershipconcentration on ERM disclosure.The population of this research was all manufacturing companies listed inthe Indonesia Stock Exchange 2011-2012. The sampling technique used in this research was puposive sampling.There were 90 companies qualified as samples. This study used multiple regression analysis to determinethe influence of firm size, RMC, auditor reputation and ownership concentration on ERM disclosure. Theresults of regression analysis showed that the variables of firm size, RMC, auditor reputation and ownershipconcentration had positive effects on the ERM disclosure.